1998
DOI: 10.1177/03635465980260022001
|View full text |Cite
|
Sign up to set email alerts
|

Meniscal Repair in the Goat Model

Abstract: We evaluated the effect of adjunctive healing measures on central tears of the adult goat medial meniscus and the role of magnetic resonance arthrography in the assessment of menisci that have undergone a repair. Peripheral tears were made unilaterally in the medial menisci of seven goats in Group I and repaired with nonabsorbable suture. Six Group II goats had central medial meniscal tears repaired as in Group I plus an exogenous fibrin clot. Eight Group III goats had central tears plus abrasion of the parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The use of a fibrin clot can also be an effective technique to support a reparative response in the avascular zone of the meniscus [34, 35, 37]. Findings demonstrated that the rasping technique is more effective than fibrin clot application to improve meniscal healing [179]. Kobayashi et al reported healing rates in the peripheral zone of the menisci in an on-organ culture model.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a fibrin clot can also be an effective technique to support a reparative response in the avascular zone of the meniscus [34, 35, 37]. Findings demonstrated that the rasping technique is more effective than fibrin clot application to improve meniscal healing [179]. Kobayashi et al reported healing rates in the peripheral zone of the menisci in an on-organ culture model.…”
Section: Discussionmentioning
confidence: 99%
“…Infiltration of the joint by the paramagnetic contrast can increase the sensitivity and specificity of the exam. In an experimental model using goats, Ritchie 21 demonstrated the 100% accuracy of arthro-MRI for the evaluation of complete meniscal healing, compared with 33% for conventional MRI. The diagnosis of a lesion or failed healing is done by visualizing the penetration of contrast medium at the site of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Synovial abrasion has been proposed as one method to improve healing response, because many growth factors are released and neovascularization is observed. 97 Trephination allows communication between the vascular peripheral third and the avascular zone. Its theoretical advantage is to reconduct the vascular flow through the white zone.…”
Section: How To Enhance Meniscal Healingmentioning
confidence: 99%
“…102 Its use has demonstrated increased healing in peripheral tears both in animal models and human patients. 97,103,104 However, in central tears its rate of success diminishes, probably influenced by the fact that healing in the inner third is different from the peripheral zone. 97…”
Section: How To Enhance Meniscal Healingmentioning
confidence: 99%